Responsibility for Life in the Economy of Sustainability - Cossiga, Giovanni Antonio (Archives of Business Research, 2023)
The responsibility for the survival of humankind is great. In concrete terms, this heavy burden lies above all in the behavior of the majorities in each community. So long as? Life must cross oceans of years and experiences. For this trip, we must believe that the majority of communities hold the responsibility on the issue of life in the future. Regarding the economy, the majority are the recipients of explicit or implicit messages concerning long-term sustainability. Messages that come from nature and are modulated by universal constants, no different from those affecting physics and matter. They are the same ones that allowed life on the planet. Sustainability for the economy in turn means having to follow the path traced for development, i.e., constant growth with the least damage to nature; a way that can accelerate the potentials and possibilities of knowledge. Leaving this classic line means falling into what we have called: the subworld. Because of this fall, the line of development rolls up on itself to become the cycle of the conjuncture; next to it often appear the two maidservants of the economic cycle, Inflation and Deflation. We have learned to get out of the long spirals of inflation in the 60s and 70s, now we face a new enemy, deflation. The struggle with deflation must follow the same line as that of getting rid of the game of inflation. Do not loosen monetary policy, but on the contrary keep it compatibly tight. On the side of the economy of sustainability, the survival of life is also achieved by winning the battle against monetary anomalies that nullify development potential. Not only. Because relations between communities and between different areas and continents worsened. On the other hand, in terms of good relations, we must look favorably on the leap forward in Southeast Asia and China, and on development prospects in Africa.